(untitled) (Homoeopathy for All, 2024)
Ammi visnaga, also known as khella, has long been used in numerous medicinal systems due to its therapeutic characteristics. Ammi visnaga has acquired popularity in homeopathy due to its capacity to treat a variety of ailments such as respiratory disorders, cardiovascular troubles, and urinary tract problems. The purpose of this review is to investigate the pharmacological qualities and clinical evidence that support the use of Ammi visnaga in homeopathic practice. This research examines the pharmacological activities, traditional usage, and therapeutic studies of Ammi visnaga based on current literature. It also highlights the challenges and potential directions for study in this field. Overall, this analysis sheds light on the therapeutic potential of Ammi visnaga in homeopathy and recommends areas for additional inquiry.